STRUKTUR MODAL DAN KINERJA PERUSAHAAN SEKTOR KESEHATAN - Jusuf, A An Arief; Natalia, Irene (Bajang Institute, 2025)
Capital structure policy relates to the source of a company's funds and management's efforts to maintain and improve its performance. Compared to the issuance of common stock, liabilities have interest expense consequences. This topic is important and timeless to research, tracking business dynamics over time. This study aims to examine the effect of capital structure on company performance. The sample of this study is healthcare companies listed on the Indonesia Stock Exchange for the period 2015-2024. The healthcare sector is one of the sectors that experienced an extreme surge from pre-health crisis conditions, then experienced an extreme decline to post-health crisis conditions. Unbalanced panel data testing was conducted using a fixed effect model. The results showed that leverage negatively affected the performance of healthcare companies during the same period. Additional testing showed that leverage had a negative effect on all company sizes, with the greatest negative impact felt by companies above average size (between 50% and 75%). The use of debt as a performance lever requires careful management response, taking company size into account.